A thermal insulation tile composite material containing a buffer layer and a preparation method thereof
Through the combination of modified buffer fibers and the thermal insulation material layer and the cooperation of modified hafnium carbide and phenolic resin, the problem of binding surface cracking caused by thermal stress during the rapid cooling of existing heat insulation materials is solved, and the overall stability and bonding performance are improved.
Patent Information
- Application Number
- CN202411579856.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing thermal insulation materials have thermal stress during the rapid cooling process, causing cracking or damage to the bonding surface, and insufficient overall stability and bonding performance.
The binding of modified buffer fibers with rigid matrix layer and toughened shell layer is adopted, and the bonding performance of the buffer layer with matrix layer and shell layer is improved through chemical bonding, physical adsorption and fiber entanglement. The combination of modified hafnium carbide and phenolic resin is used in the impregnation molding step to optimize the bonding performance between each layer.
It effectively improves the thermal matching problem between the buffer layer and the rigid heat-insulating tile substrate and the toughened shell, improves overall stability, avoids cracking or damage of the bonding surface during rapid cooling, and improves the performance of the heat-insulating material.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of heat insulation materials, in particular to a heat insulation tile composite material containing a buffer layer and a preparation method thereof. Background Art
[0002] Aerospace vehicles face severe aerodynamic heating when flying through the atmosphere at high Mach numbers. Thermal protection systems are key to ensuring the safety of aerospace vehicle structures, equipment, and personnel. The thermal protection system of aerospace vehicles includes: an outer protective layer and a thermal insulation layer. The thermal insulation layer is usually a rigid thermal insulation tile, aerogel, or a flexible fiber felt. For the thermal insulation layer, the use of lightweight and efficient thermal insulation materials helps to increase the payload of aerospace vehicles and improve their flight speed and flight stability.
[0003] Rigid thermal insulation tiles are typical representatives of materials used in thermal insulation layers in aerospace thermal protection systems and are currently used in large quantities in aerospace thermal protection systems. Aerogel is a nanoporous material with the characteristics of light weight, high porosity, and high specific surface area. Its thermal conductivity is extremely low and it is effectively suitable for use as the preferred material for thermal insulation layers in aerospace thermal protection systems. Flexible fiber felt is a fiber felt or fiber blanket made of high-temperature resistant ceramic fiber through wet molding or needle punching. It is compressible, deformable, and flexible.
[0004] With the continuous development of aerospace thermal protection technology, higher requirements have been put forward for the temperature resistance, thermal insulation performance, thermal insulation stability, mechanical properties, durability, etc. of thermal insulation materials. Thermal insulation materials made of a single material have gradually been unable to meet the requirements of existing aerospace technology. Rigid thermal insulation tiles are inherently brittle, and in actual use, due to external factors such as aerodynamic forces and vibration-coupled loads, they cannot effectively disperse and absorb impact forces, and cannot effectively protect sensitive structures and precision equipment in aerospace vehicles. Aerogels have limited compressibility and poor matching performance with the outer protective layer. Flexible fiber felts have high thermal conductivity and unsatisfactory thermal insulation performance.
[0005] In order to overcome the defects of the aforementioned rigid insulation tiles, the prior art discloses related technologies for preparing composite insulation materials by combining a rigid insulation tile matrix with a buffer layer. In the composite insulation material, the buffer layer cooperates with the rigid insulation tile matrix to disperse and absorb the impact force received by the aerospace vehicle during flight, thereby improving flight safety and further optimizing the insulation protection effect. However, there are thermal matching problems between the buffer layer and the rigid insulation tile matrix, as well as between the buffer layer and the protective toughened shell. The overall stability of the composite insulation material is poor. During the rapid heating and cooling process, thermal stress will be generated inside the composite insulation material, resulting in cracking or damage to the bonding surface between the buffer layer and the rigid insulation tile matrix or the toughened shell, and the performance of the composite insulation material is significantly reduced. At the same time, the bonding performance between the buffer layer and the rigid insulation tile matrix or the toughened shell also needs to be further improved. Summary of the invention
[0006] In order to solve the technical problems existing in the prior art, the present invention provides a thermal insulation tile composite material containing a buffer layer and a preparation method thereof, which can effectively improve the thermal matching problem between the buffer layer and the rigid thermal insulation tile substrate, and between the buffer layer and the protective toughened shell, thereby improving the overall stability; effectively avoid cracking or damage to the bonding surface between the buffer layer and the rigid thermal insulation tile substrate or the toughened shell during rapid heating and cooling, thereby avoiding degradation of the performance of the thermal insulation material; and further improve the bonding performance between the buffer layer and the rigid thermal insulation tile substrate or the toughened shell.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a heat-insulating tile composite material containing a buffer layer comprises the following steps: preparing modified buffer fibers, preparing a composite molded body, preparing a toughened shell, and impregnating and molding.
[0009] The method for preparing the modified buffer fiber comprises the following steps: twisting and blending fused quartz glass fiber and aromatic sulfone fiber at a weight ratio of 1:2-2.5, controlling the number of strands of the blended fiber to be 10-14, to obtain composite fiber; then chopping the composite fiber to 80-90 mm, to obtain chopped composite fiber; then putting the chopped composite fiber into a 15-20 times by weight hydrogen peroxide solution, stirring and heating to 90-95° C., keeping the temperature under reflux and stirring for 2-3 hours, separating solid matter, washing the solid matter 2-3 times with 7-8 times by weight of deionized water, placing the solid matter in a vacuum drying oven, and drying the solid matter at 80-85° C. to constant weight in a vacuum environment of 0.085-0.095 MPa, to obtain the modified buffer fiber.
[0010] In the preparation of the modified buffer fiber, the concentration of the hydrogen peroxide solution is 3-3.5wt%.
[0011] The method for preparing the composite molded body comprises: chopping aluminum borosilicate fiber, mullite fiber and alumina fiber into 50-70 mm pieces respectively, and then mixing them with polyacrylic acid, bis(dioctyl pyrophosphate acyloxy)ethylene titanate and deionized water to obtain a mixed slurry; then introducing the mixed slurry into a mold, filtering and molding, and then transferring the mixed slurry into a constant temperature drying oven, drying at 120-130° C. for 35-36 hours, and demolding to obtain a preform; then placing the preform into a calcining furnace, heating the preform to 200 ° C., and heating the preform to 300 ° C. The temperature is raised to 1000-1100°C, calcined for 2-3 hours, and cooled to room temperature with the furnace to obtain a lower layer blank; then the modified buffer fiber is layered on the lower layer blank to form a buffer layer; and the layer thickness of the modified buffer fiber is controlled to be 10-12mm. After the layering is completed, it is impregnated with deionized water and then pressed, and then placed in a constant temperature box, heated to 100-105°C, and heat-preserved for 10-12 hours to obtain a composite molded body with an upper buffer layer and a lower rigid matrix layer.
[0012] In the preparation of the composite molded body, the weight ratio of aluminum borosilicate fiber, mullite fiber, alumina fiber, polyacrylic acid, bis(dioctyl pyrophosphate acyloxy)ethylene titanate, and deionized water is 38-40:50-52:12-15:0.6-0.7:3-3.5:3500-3600;
[0013] The diameter of aluminum borosilicate fiber is 2-3 μm; the diameter of mullite fiber is 4-5 μm; the diameter of alumina fiber is 9-10 μm.
[0014] The method for preparing the toughened shell comprises the following steps: adding terminal hydroxyl polysiloxane and nano silicon carbide into cyclohexane, dispersing them uniformly, and obtaining a toughened coating; then coating the toughened coating on the outer surface of the upper buffer layer of the composite molded body, and controlling the penetration depth of the toughened coating into the buffer layer of the composite molded body to be 0.7-0.75 mm; then transferring the composite shell to a constant temperature box, heat-preserving and curing at 110-115° C. for 4-5 hours, and obtaining a composite precursor having an upper toughened shell layer, a middle buffer layer, and a lower rigid substrate layer.
[0015] In the preparation of the toughened shell, the weight ratio of terminal hydroxyl polysiloxane, nano silicon carbide and cyclohexane is 100:8.5-9:72-76.
[0016] The impregnation molding method comprises the following steps: adding sodium bicarbonate, hexadecyltrimethylammonium chloride and modified hafnium carbide into deionized water, stirring evenly, adding phenolic resin and silane coupling agent KH-550, and continuing stirring for 50-60 minutes to obtain an impregnation solution; then impregnating a composite precursor into 1.8-2 times the volume of the impregnation solution, and vacuum impregnating the composite precursor for 2-3 hours under a vacuum degree of 0.04-0.05MPa, taking out the composite precursor and transferring it into a constant temperature box, standing at room temperature for 10-12 hours, heating it to 90-95°C, keeping it at this temperature and keeping it at this temperature for 9-10 hours, transferring it into a calcining furnace, heating it to 400-450°C in an argon atmosphere, keeping it at this temperature and calcining it for 2-2.5 hours, and cooling it to room temperature with the furnace to obtain a heat-insulating tile composite material containing a buffer layer.
[0017] In the dipping molding, the weight ratio of sodium bicarbonate, hexadecyltrimethylammonium chloride, modified hafnium carbide, deionized water, phenolic resin, and silane coupling agent KH-550 is 1.2-1.3:0.5-0.6:7.5-8:55-58:100-105:13-15;
[0018] The phenolic resin is a phenolic resin prepolymer with a molecular weight of 300-400.
[0019] The preparation method of the modified hafnium carbide comprises the following steps: adding nano hafnium carbide to 80-85 times the weight of anhydrous ethanol, uniformly dispersing the nano hafnium carbide by ultrasonication, and then dripping a first liquid therein with stirring; after the first liquid is dripped therein, continuing to drip the second liquid therein with stirring, and controlling the dripping time of the second liquid to be 30-40 minutes; after the second liquid is dripped therein, reacting for 22-24 hours under the temperature condition of 8-10° C. with temperature control and stirring, separating out solid matter, washing the solid matter with 7-8 times the weight of anhydrous ethanol, transferring the solid matter to a constant temperature box, keeping the temperature at 70-75° C. for 1.5-2 hours, transferring the solid matter to a roasting furnace, keeping the temperature at 270-280° C. for 2.5-3 hours, cooling the solid matter to room temperature with the furnace, and grinding the solid matter to obtain the modified hafnium carbide.
[0020] In the preparation of the modified hafnium carbide, the first liquid is a solution of pyromellitic anhydride in N,N-dimethylacetamide (DMAC); the mass concentration of pyromellitic anhydride in the first liquid is 4-4.1wt%;
[0021] The second liquid is a solution of 4,4'-diaminodiphenyl ether in N,N-dimethylacetamide (DMAC); the mass concentration of 4,4'-diaminodiphenyl ether in the second liquid is 3.5-3.6wt%;
[0022] The weight ratio of the nano-hafnium carbide to the pyromellitic anhydride in the first liquid and the 4,4'-diaminodiphenyl ether in the second liquid is 83-85:56.5-57:51.5-52.
[0023] A heat-insulating tile composite material containing a buffer layer is prepared by the above-mentioned preparation method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The thermal insulation tile composite material containing a buffer layer of the present invention and its preparation method, select fused silica glass fiber and aromatic sulfone fiber, twist and blend, cut into short composite fibers, and then use hydrogen peroxide to modify the hydroxyl groups to obtain modified buffer fibers, which can improve the bonding performance of the modified buffer fibers with the rigid matrix layer, the toughened shell layer and the phenolic aerogel material, and improve the bonding and matching performance of the buffer layer with the rigid matrix layer and the toughened shell layer through chemical bonding, physical adsorption and fiber entanglement; then in the step of preparing the composite molded body , aluminum borosilicate fiber, mullite fiber, and alumina fiber are selected to prepare a lower layer blank (i.e., a rigid matrix layer), and then a buffer layer is prepared on the basis of the rigid matrix layer; then in the step of preparing a toughened shell, a toughened coating is prepared by combining terminal hydroxyl polysiloxane with nano silicon carbide, and then a toughened shell layer is prepared on the basis of the buffer layer, forming a composite precursor with an upper toughened shell layer, a middle buffer layer, and a lower rigid matrix layer; then in the impregnation molding step, modified hafnium carbide is combined with phenolic resin to prepare a toughened shell layer. A phenolic aerogel precursor liquid (i.e., an impregnation liquid) is prepared, and a thermal insulation tile composite material containing a buffer layer is obtained by impregnating, curing, and calcining the composite precursor with the precursor, thereby further improving the bonding performance between the layers in the thermal insulation tile composite material; at the same time, polyimide is used to coat and modify the nano-hafnium carbide to improve the bonding performance between the nano-hafnium carbide and the phenolic aerogel, and to improve the dispersion of the modified hafnium carbide in the phenolic aerogel, while optimizing the physical properties and thermal conductivity of the thermal insulation tile composite material, further improving the buffer layer through the cooperation of the phenolic aerogel and the buffer layer. The bonding and matching performance between the punching layer and the rigid base layer and the toughened outer shell layer; the aforementioned technical means cooperate and work synergistically with each other to effectively improve the thermal matching problem between the buffer layer and the rigid insulation tile base, as well as between the buffer layer and the protective toughened outer shell, and improve the overall stability; effectively avoid cracking or damage to the bonding surface between the buffer layer and the rigid insulation tile base or the toughened outer shell during rapid heating and cooling, and avoid degradation of the performance of the thermal insulation material; and further improve the bonding performance between the buffer layer and the rigid insulation tile base or the toughened outer shell.
[0026] (2) The thermal conductivity of the heat-insulating tile composite material containing a buffer layer of the present invention is 0.031-0.033 W / (m·k), the tensile strength in the thickness direction is 1.17-1.20 MPa, and the fracture toughness is 1.02-1.04 MPa·m 1 / 2 The interface bonding strength between the buffer layer and the rigid substrate layer is 4.5-4.8MPa, and the interface bonding strength between the buffer layer and the toughened shell layer is 3.1-3.2MPa.
[0027] (3) After the thermal insulation tile composite material containing a buffer layer of the present invention is subjected to 20 thermal shock cycles of rapid temperature rise and fall (1200°C to room temperature), there is no cracking or damage on the bonding surface between the buffer layer and the rigid base layer, and there is no cracking or damage on the bonding surface between the buffer layer and the toughened outer shell layer. The interface bonding strength between the buffer layer and the rigid base layer is 4.2-4.5 MPa, and the interface bonding strength between the buffer layer and the toughened outer shell is 2.9-3.0 MPa. The tensile strength of the thermal insulation tile composite material in the thickness direction is 1.10-1.13 MPa.
[0028] (4) After the thermal insulation tile composite material containing a buffer layer of the present invention is subjected to 20 thermal shock cycles (1200°C to room temperature) of rapid temperature rise and fall, the difference (absolute value) in the heating permanent line change between the buffer layer and the rigid base layer is 0.004-0.005%, and the difference (absolute value) in the heating permanent line change between the buffer layer and the toughened outer shell layer is 0.006-0.007%. DETAILED DESCRIPTION
[0029] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0030] Example 1
[0031] This embodiment provides a method for preparing a thermal insulation tile composite material containing a buffer layer, specifically:
[0032] 1. Preparation of modified buffer fiber
[0033] The fused silica glass fiber and the aromatic sulfone fiber with a weight ratio of 1:2 are twisted and blended, and the number of the blended fiber strands is controlled to be 10 to obtain a composite fiber; the composite fiber is then chopped into 80 mm to obtain a chopped composite fiber; the chopped composite fiber is then put into a 15-times-by-weight hydrogen peroxide solution, stirred and heated to 90°C, kept refluxed and stirred for 2 hours, and the solid matter is separated, and the solid matter is washed twice with 7-times-by-weight deionized water, and then placed in a vacuum drying oven, and dried at 80°C to constant weight in a vacuum environment of 0.085 MPa to obtain a modified buffer fiber.
[0034] Wherein, the concentration of the hydrogen peroxide solution is 3wt%.
[0035] 2. Preparation of composite molded body
[0036] Aluminum borosilicate fiber, mullite fiber and alumina fiber were chopped to 50 mm respectively, and then mixed with polyacrylic acid, bis(dioctyl pyrophosphate)ethylene titanate and deionized water to obtain a mixed slurry; then the mixed slurry was introduced into a mold, filtered and formed, and then transferred to a constant temperature drying oven, dried at 120°C for 35 hours, demolded, and a preform was obtained; then the preform was placed in a calcining furnace, heated to 1000°C, kept warm and calcined for 2 hours, and cooled to room temperature with the furnace to obtain a lower layer blank; then the modified buffer fiber was layered on the lower layer blank to form a buffer layer; and the layer thickness of the modified buffer fiber was controlled to be 10 mm. After the layering was completed, it was wetted with deionized water and pressed, and then placed in a constant temperature box, heated to 100°C, kept warm and shaped for 10 hours, to obtain a composite molded body with an upper buffer layer and a lower rigid matrix layer.
[0037] Wherein, the weight ratio of aluminum borosilicate fiber, mullite fiber, alumina fiber, polyacrylic acid, bis(dioctyl pyrophosphate)ethylene titanate and deionized water is 38:50:12:0.6:3:3500.
[0038] The diameter of the aluminum borosilicate fiber is 2 μm; the diameter of the mullite fiber is 5 μm; and the diameter of the alumina fiber is 10 μm.
[0039] 3. Prepare toughened shell
[0040] End hydroxyl polysiloxane and nano silicon carbide are put into cyclohexane and dispersed evenly to obtain a toughened coating; the toughened coating is then applied to the outer surface of the upper buffer layer of the composite molded body, and the depth of the toughened coating penetrating into the buffer layer of the composite molded body is controlled to be 0.7 mm; then the composite precursor is transferred to a constant temperature box and cured at 110°C for 4 hours to obtain a toughened outer shell layer on the upper layer, a buffer layer in the middle layer, and a rigid base layer on the lower layer.
[0041] Wherein, the weight ratio of terminal hydroxyl polysiloxane, nano silicon carbide and cyclohexane is 100:8.5:72.
[0042] 4. Dipping molding
[0043] Sodium bicarbonate, hexadecyltrimethylammonium chloride and modified hafnium carbide are put into deionized water, stirred evenly, and then phenolic resin and silane coupling agent KH-550 are added, and stirring is continued for 50 minutes to obtain an impregnation solution; then the composite precursor is impregnated into 1.8 times the volume of the impregnation solution, and vacuum impregnation is performed for 2 hours under a vacuum degree of 0.04MPa. The composite precursor is taken out and transferred to a constant temperature box, and after standing at room temperature for 10 hours, the temperature is increased to 90°C, and after being kept at this temperature for 9 hours, it is transferred to a calcination furnace, and in an argon atmosphere, the temperature is increased to 400°C, and after being kept at this temperature for calcination for 2 hours, it is cooled to room temperature with the furnace to obtain a thermal insulation tile composite material containing a buffer layer.
[0044] Wherein, the weight ratio of sodium bicarbonate, hexadecyltrimethylammonium chloride, modified hafnium carbide, deionized water, phenolic resin and silane coupling agent KH-550 is 1.2:0.5:7.5:55:100:13.
[0045] The phenolic resin is a phenolic resin prepolymer with a molecular weight of 400.
[0046] The preparation method of modified hafnium carbide is as follows: adding nano hafnium carbide into 80 times the weight of anhydrous ethanol, uniformly dispersing it by ultrasonication, and then dripping in a first liquid with stirring; after the first liquid is dripped in, the second liquid is dripped in with continued stirring, and the dripping time of the second liquid is controlled to be 30 minutes; after the second liquid is dripped in, the reaction is carried out under the temperature condition of 8°C with temperature control and stirring for 22 hours, and then the solid matter is separated, and the solid matter is washed with 7 times the weight of anhydrous ethanol, and then transferred to a constant temperature box, kept at 70°C for 1.5 hours, and then transferred to a roasting furnace, kept at 270°C for 2.5 hours, cooled to room temperature with the furnace, and ground evenly to obtain modified hafnium carbide.
[0047] The first liquid is a solution of pyromellitic anhydride in N,N-dimethylacetamide (DMAC); the mass concentration of pyromellitic anhydride in the first liquid is 4 wt %.
[0048] The second liquid is a solution of 4,4'-diaminodiphenyl ether in N,N-dimethylacetamide (DMAC); the mass concentration of 4,4'-diaminodiphenyl ether in the second liquid is 3.5 wt %.
[0049] The weight ratio of the nano-hafnium carbide to the pyromellitic anhydride in the first liquid and the 4,4'-diaminodiphenyl ether in the second liquid is 83:56.5:51.5.
[0050] This embodiment also provides a thermal insulation tile composite material containing a buffer layer produced by the aforementioned method.
[0051] Example 2
[0052] This embodiment provides a method for preparing a thermal insulation tile composite material containing a buffer layer, specifically:
[0053] 1. Preparation of modified buffer fiber
[0054] The fused silica glass fiber and the aromatic sulfone fiber with a weight ratio of 1:2.2 are twisted and blended, and the number of the blended fiber strands is controlled to be 12 to obtain a composite fiber; the composite fiber is then chopped into 85 mm to obtain a chopped composite fiber; the chopped composite fiber is then put into an 18-fold weight hydrogen peroxide solution, stirred and heated to 92°C, kept refluxed and stirred for 2.5 hours, and the solid is separated. The solid is washed three times with 7.5-fold weight of deionized water, and then placed in a vacuum drying oven, and dried at 82°C to constant weight in a vacuum environment of 0.09 MPa to obtain a modified buffer fiber.
[0055] Wherein, the concentration of hydrogen peroxide solution is 3.2wt%.
[0056] 2. Preparation of composite molded body
[0057] Aluminum borosilicate fiber, mullite fiber and alumina fiber were chopped to 60 mm respectively, and then mixed with polyacrylic acid, bis(dioctyl pyrophosphate)ethylene titanate and deionized water to obtain a mixed slurry; the mixed slurry was then introduced into a mold, filtered and formed, and then transferred to a constant temperature drying oven, dried at 125°C for 35.5 hours, and demolded to obtain a preform; the preform was then placed in a calcining furnace, heated to 1050°C, kept warm and calcined for 2.5 hours, and cooled to room temperature with the furnace to obtain a lower layer blank; the modified buffer fiber was then layered on the lower layer blank to form a buffer layer; and the layer thickness of the modified buffer fiber was controlled to be 11 mm. After the layering was completed, it was wetted with deionized water and pressed, and then placed in a constant temperature box, heated to 102°C, and kept warm for 11 hours to obtain a composite molded body with an upper buffer layer and a lower rigid matrix layer.
[0058] Among them, the weight ratio of aluminum borosilicate fiber, mullite fiber, alumina fiber, polyacrylic acid, bis(dioctyl pyrophosphate)ethylene titanate and deionized water is 39:51:13:0.65:3.3:3550.
[0059] The diameter of the aluminum borosilicate fiber is 2 μm; the diameter of the mullite fiber is 5 μm; and the diameter of the alumina fiber is 10 μm.
[0060] 3. Prepare toughened shell
[0061] End hydroxyl polysiloxane and nano silicon carbide are put into cyclohexane and dispersed evenly to obtain a toughened coating; the toughened coating is then applied to the outer surface of the upper buffer layer of the composite molded body, and the depth of the toughened coating penetrating into the buffer layer of the composite molded body is controlled to be 0.72 mm; then the composite precursor is transferred to a constant temperature box and cured at 112°C for 4.5 hours to obtain a composite precursor with a toughened outer shell layer on the upper layer, a buffer layer in the middle layer, and a rigid base layer on the lower layer.
[0062] Wherein, the weight ratio of terminal hydroxyl polysiloxane, nano silicon carbide and cyclohexane is 100:8.7:75.
[0063] 4. Dipping molding
[0064] Sodium bicarbonate, hexadecyltrimethylammonium chloride and modified hafnium carbide are put into deionized water, stirred evenly, and then phenolic resin and silane coupling agent KH-550 are added, and stirring is continued for 55 minutes to obtain an impregnation solution; then the composite precursor is impregnated into 1.9 times the volume of the impregnation solution, and vacuum impregnation is performed for 2.5 hours under a vacuum degree of 0.045 MPa. The composite precursor is taken out and transferred to a constant temperature box, and after standing at room temperature for 11 hours, the temperature is increased to 92°C, and after being kept at this temperature for 9.5 hours, it is transferred to a calcination furnace, and in an argon atmosphere, the temperature is increased to 430°C, and after being kept at this temperature for calcination for 2.3 hours, it is cooled to room temperature with the furnace to obtain a thermal insulation tile composite material containing a buffer layer.
[0065] Wherein, the weight ratio of sodium bicarbonate, hexadecyltrimethylammonium chloride, modified hafnium carbide, deionized water, phenolic resin and silane coupling agent KH-550 is 1.25:0.55:7.7:56:103:14.
[0066] The phenolic resin is a phenolic resin prepolymer with a molecular weight of 400.
[0067] The preparation method of modified hafnium carbide is as follows: adding nano hafnium carbide into 82 times the weight of anhydrous ethanol, uniformly dispersing it by ultrasonication, and then dripping in a first liquid with stirring; after the first liquid is dripped in, the second liquid is dripped in with continued stirring, and the dripping time of the second liquid is controlled to be 35 minutes; after the second liquid is dripped in, the reaction is carried out under a temperature condition of 9°C with temperature control and stirring for 23 hours, and then the solid matter is separated, and the solid matter is washed with 7.5 times the weight of anhydrous ethanol, and then transferred to a constant temperature box, kept at 72°C for 1.8 hours, and then transferred to a roasting furnace, kept at 275°C for 2.8 hours, cooled to room temperature with the furnace, and ground evenly to obtain modified hafnium carbide.
[0068] The first liquid is a solution of pyromellitic anhydride in N,N-dimethylacetamide (DMAC); the mass concentration of pyromellitic anhydride in the first liquid is 4.05 wt %.
[0069] The second liquid is a solution of 4,4'-diaminodiphenyl ether in N,N-dimethylacetamide (DMAC); the mass concentration of 4,4'-diaminodiphenyl ether in the second liquid is 3.55 wt %.
[0070] The weight ratio of the nano-hafnium carbide to the pyromellitic anhydride in the first liquid and the 4,4'-diaminodiphenyl ether in the second liquid is 84:56.8:51.8.
[0071] This embodiment also provides a thermal insulation tile composite material containing a buffer layer produced by the aforementioned method.
[0072] Example 3
[0073] This embodiment provides a method for preparing a thermal insulation tile composite material containing a buffer layer, specifically:
[0074] 1. Preparation of modified buffer fiber
[0075] The fused silica glass fiber and the aromatic sulfone fiber with a weight ratio of 1:2.5 are twisted and blended, and the number of the blended fiber strands is controlled to be 14 to obtain a composite fiber; the composite fiber is then chopped into 90 mm to obtain a chopped composite fiber; the chopped composite fiber is then put into a 20 times by weight hydrogen peroxide solution, stirred and heated to 95°C, kept refluxed and stirred for 3 hours, and the solid matter is separated, and the solid matter is washed 3 times with 8 times by weight of deionized water, and then placed in a vacuum drying oven, and dried at 85°C to constant weight in a vacuum environment of 0.095 MPa to obtain a modified buffer fiber.
[0076] Wherein, the concentration of the hydrogen peroxide solution is 3.5wt%.
[0077] 2. Preparation of composite molded body
[0078] Aluminum borosilicate fiber, mullite fiber and alumina fiber were chopped to 70 mm respectively, and then mixed with polyacrylic acid, bis(dioctyl pyrophosphate)ethylene titanate and deionized water to obtain a mixed slurry; the mixed slurry was then introduced into a mold, filtered and formed, and then transferred to a constant temperature drying oven, dried at 130°C for 36 hours, and demolded to obtain a preform; the preform was then placed in a calcining furnace, heated to 1100°C, kept warm and calcined for 3 hours, and cooled to room temperature with the furnace to obtain a lower layer blank; the modified buffer fiber was then layered on the lower layer blank to form a buffer layer; and the layer thickness of the modified buffer fiber was controlled to be 12 mm. After the layering was completed, it was wetted with deionized water and pressed, and then placed in a constant temperature box, heated to 105°C, kept warm and shaped for 12 hours to obtain a composite molded body with an upper buffer layer and a lower rigid matrix layer.
[0079] Wherein, the weight ratio of aluminum borosilicate fiber, mullite fiber, alumina fiber, polyacrylic acid, bis(dioctyl pyrophosphate)ethylene titanate and deionized water is 40:52:15:0.7:3.5:3600.
[0080] The diameter of the aluminum borosilicate fiber is 2 μm; the diameter of the mullite fiber is 5 μm; and the diameter of the alumina fiber is 10 μm.
[0081] 3. Prepare toughened shell
[0082] End hydroxyl polysiloxane and nano silicon carbide are put into cyclohexane and dispersed evenly to obtain a toughened coating; the toughened coating is then applied to the outer surface of the upper buffer layer of the composite molded body, and the depth of the toughened coating penetrating into the buffer layer of the composite molded body is controlled to be 0.75 mm; then the composite precursor is transferred to a constant temperature box and cured at 115°C for 5 hours to obtain a toughened outer shell layer on the upper layer, a buffer layer in the middle layer, and a rigid base layer on the lower layer.
[0083] Wherein, the weight ratio of terminal hydroxyl polysiloxane, nano silicon carbide and cyclohexane is 100:9:76.
[0084] 4. Dipping molding
[0085] Sodium bicarbonate, hexadecyltrimethylammonium chloride and modified hafnium carbide are put into deionized water, stirred evenly, and then phenolic resin and silane coupling agent KH-550 are added, and stirring is continued for 60 minutes to obtain an impregnation solution; then the composite precursor is impregnated into 2 times the volume of the impregnation solution, and vacuum impregnation is carried out for 3 hours under a vacuum degree of 0.05MPa. The composite precursor is taken out and transferred to a constant temperature box, and after standing at room temperature for 12 hours, the temperature is increased to 95°C, and after being kept at this temperature for 10 hours, it is transferred to a calcination furnace, and in an argon atmosphere, the temperature is increased to 450°C, and after being kept at this temperature for calcination for 2.5 hours, it is cooled to room temperature with the furnace to obtain a thermal insulation tile composite material containing a buffer layer.
[0086] Wherein, the weight ratio of sodium bicarbonate, hexadecyltrimethylammonium chloride, modified hafnium carbide, deionized water, phenolic resin and silane coupling agent KH-550 is 1.3:0.6:8:58:105:15.
[0087] The phenolic resin is a phenolic resin prepolymer with a molecular weight of 400.
[0088] The preparation method of modified hafnium carbide is as follows: adding nano hafnium carbide into 85 times the weight of anhydrous ethanol, uniformly dispersing by ultrasonication, and then dripping in a first liquid with stirring; after the first liquid is dripped in, the second liquid is dripped in with continued stirring, and the dripping time of the second liquid is controlled to be 40 minutes; after the second liquid is dripped in, the reaction is carried out under temperature conditions of 10°C with temperature control and stirring for 24 hours, and then the solid is separated, and the solid is washed with 8 times the weight of anhydrous ethanol, and then transferred to a constant temperature box, kept at 75°C for 2 hours, and then transferred to a roasting furnace, kept at 280°C for 3 hours, cooled to room temperature with the furnace, and ground evenly to obtain modified hafnium carbide.
[0089] The first liquid is a solution of pyromellitic anhydride in N,N-dimethylacetamide (DMAC); the mass concentration of pyromellitic anhydride in the first liquid is 4.1 wt %.
[0090] The second liquid is a solution of 4,4'-diaminodiphenyl ether in N,N-dimethylacetamide (DMAC); the mass concentration of 4,4'-diaminodiphenyl ether in the second liquid is 3.6 wt %.
[0091] The weight ratio of the nano-hafnium carbide to the pyromellitic dianhydride in the first liquid and the 4,4'-diaminodiphenyl ether in the second liquid is 85:57:52.
[0092] This embodiment also provides a thermal insulation tile composite material containing a buffer layer produced by the aforementioned method.
[0093] Comparative Example 1
[0094] The technical scheme of Example 2 is adopted, but the differences are as follows: 1) the step of preparing modified buffer fibers is omitted, and fused quartz glass fibers are used instead of modified buffer fibers for the subsequent step of preparing a composite molded body; 2) in the step of preparing a composite molded body, aluminum borosilicate fibers and bis(dioctyl pyrophosphate)ethylene titanate are omitted, and alumina fibers are used to supplement the weight of aluminum borosilicate fibers.
[0095] Comparative Example 2
[0096] The technical solution of Example 2 is adopted, but the differences are: 1) in the step of preparing the modified buffer fiber, the aromatic sulfone fiber and the twisting and blending process are omitted; 2) in the impregnation molding step, the preparation of the modified hafnium carbide is omitted, and unmodified nano hafnium carbide is used instead of the modified hafnium carbide to prepare the impregnation solution.
[0097] The thermal conductivity, thickness tensile strength, fracture toughness, interface bonding strength between the buffer layer and the rigid substrate layer, and interface bonding strength between the buffer layer and the toughened outer shell layer of the thermal insulation tile composite materials containing buffer layers of Examples 1-3 and Comparative Examples 1-2 were tested respectively. The fracture toughness was tested using the single edge notched beam method (SENB method). The specific results are shown in the following table:
[0098]
[0099] Furthermore, the thermal insulation tile composite materials containing buffer layers of Examples 1-3 and Comparative Examples 1-2 were respectively placed in a calcination furnace, and in an air atmosphere environment, the temperature was increased to 1200°C at a heating rate of 30°C / min, and after keeping the temperature for 8 hours, the temperature was cooled to room temperature at a cooling rate of 20°C / min; the aforementioned rapid heating and cooling process was regarded as one thermal shock cycle, and after 20 consecutive thermal shock cycles, it was observed whether there was any cracking or damage on the bonding surface between the buffer layer and the rigid base layer; it was observed whether there was any cracking or damage on the bonding surface between the buffer layer and the toughened outer shell layer. The thickness direction tensile strength of the thermal insulation tile composite material containing a buffer layer, the interface bonding strength between the buffer layer and the rigid substrate layer, and the interface bonding strength between the buffer layer and the toughened outer shell layer were tested; and the heating permanent line changes of the buffer layer, the rigid substrate layer, and the toughened outer shell layer were tested using the length measuring instrument method, and the heating permanent line change difference between the buffer layer and the rigid substrate layer (the heating permanent line change value of the buffer layer minus the heating permanent line change value of the rigid substrate layer, taking the absolute value) and the heating permanent line change difference between the buffer layer and the toughened outer shell layer (the heating permanent line change value of the buffer layer minus the heating permanent line change value of the toughened outer shell layer, taking the absolute value) were calculated. The specific results are shown in the following table:
[0100]
[0101] It can be seen that in the preparation method of the heat-insulating tile composite material containing a buffer layer of the present invention, fused quartz glass fiber and aromatic sulfone fiber are selected, twisted and blended, and chopped into short composite fibers, and then hydroxyl-modified with hydrogen peroxide to obtain modified buffer fibers, which can improve the bonding performance of the modified buffer fibers with the rigid matrix layer, the toughened shell layer and the phenolic aerogel material, and improve the bonding and matching performance of the buffer layer with the rigid matrix layer and the toughened shell layer through chemical bonding, physical adsorption and fiber entanglement; then in the step of preparing the composite molded body, In the step of preparing a toughened shell, aluminum borosilicate fiber, mullite fiber, and alumina fiber are selected to prepare a lower layer blank (i.e., a rigid matrix layer), and then a buffer layer is prepared on the basis of the rigid matrix layer; then in the step of preparing a toughened shell, a toughened coating is prepared by combining terminal hydroxyl polysiloxane with nano-silicon carbide, and then a toughened shell layer is prepared on the basis of the buffer layer, forming a composite precursor with an upper toughened shell layer, a middle buffer layer, and a lower rigid matrix layer; then in the step of impregnation molding, modified hafnium carbide is combined with phenolic resin, A phenolic aerogel precursor liquid (i.e., an impregnation liquid) is prepared, and the composite precursor is impregnated, solidified, and calcined to obtain a thermal insulation tile composite material containing a buffer layer, thereby further improving the bonding performance between the layers in the thermal insulation tile composite material; at the same time, polyimide is used to coat and modify nano-hafnium carbide to improve the bonding performance between nano-hafnium carbide and phenolic aerogel, and to improve the dispersion of modified hafnium carbide in phenolic aerogel, thereby optimizing the physical properties and thermal conductivity of the thermal insulation tile composite material, and further improving the thermal insulation performance through the combination of phenolic aerogel and the buffer layer. The bonding and matching performance between the buffer layer and the rigid base layer and the toughened outer shell layer; the aforementioned technical means cooperate and work synergistically with each other to effectively improve the thermal matching problem between the buffer layer and the rigid insulation tile base, as well as between the buffer layer and the protective toughened outer shell, and improve the overall stability; effectively avoid cracking or damage to the bonding surface between the buffer layer and the rigid insulation tile base or the toughened outer shell during rapid heating and cooling, and avoid degradation of the performance of the insulation material; and further improve the bonding performance between the buffer layer and the rigid insulation tile base or the toughened outer shell.
[0102] Unless otherwise specified, all percentages used in the present invention are by mass.
[0103] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a thermal insulation tile composite material containing a buffer layer, characterized in that: The method comprises the following steps: preparing modified buffer fiber, preparing composite molded body, preparing toughened shell, and impregnating and molding; The method for preparing the modified buffer fiber comprises: twisting and blending fused silica glass fiber and aromatic sulfone fiber, and then chopping them to obtain chopped composite fiber; putting the chopped composite fiber into a hydrogen peroxide solution, stirring and heating to 90-95° C., keeping the temperature under reflux and stirring, separating solid matter, washing and drying the solid matter, and obtaining the modified buffer fiber; The method for preparing the composite molded body comprises: uniformly mixing chopped aluminum borosilicate fiber, mullite fiber, and alumina fiber with polyacrylic acid, bis(dioctyl pyrophosphate acyloxy)ethylene titanate, and deionized water to obtain a mixed slurry; introducing the mixed slurry into a mold, filtering and molding, drying, demolding, and calcining to obtain a lower layer body; laying a modified buffer fiber on the lower layer body, impregnating it with deionized water, and then pressing it, and heat-preserving and shaping it at 100-105° C. to obtain a composite molded body with an upper buffer layer and a lower rigid matrix layer; The method for preparing the toughened shell comprises: uniformly mixing terminal hydroxyl polysiloxane, nano silicon carbide and cyclohexane to obtain a toughened coating; then coating the toughened coating on the outer surface of the upper buffer layer of the composite molded body, heat-insulating and curing the composite precursor; The impregnation molding method comprises: mixing sodium bicarbonate, hexadecyltrimethylammonium chloride, modified hafnium carbide, deionized water, phenolic resin, and silane coupling agent KH-550 uniformly to obtain an impregnation solution; then impregnating a composite precursor into the impregnation solution, vacuum impregnating, taking out the composite precursor, standing at room temperature, keeping at 90-95° C., and then calcining to obtain a heat-insulating tile composite material containing a buffer layer; The preparation method of the modified hafnium carbide comprises the following steps: adding nano hafnium carbide into anhydrous ethanol, dispersing the nano hafnium carbide uniformly, and then dripping a first liquid therein with stirring; after the first liquid is dripped therein with stirring; after the second liquid is dripped therein with stirring, reacting for 22-24 hours at a temperature of 8-10° C., separating out a solid, washing and drying the solid, and then roasting at 270-280° C. for 2.5-3 hours to obtain the modified hafnium carbide; The first liquid is a solution of pyromellitic anhydride in N,N-dimethylacetamide (DMAC); The second liquid is a solution of 4,4'-diaminodiphenyl ether in N,N-dimethylacetamide (DMAC).
2. The method for preparing the thermal insulation tile composite material containing a buffer layer according to claim 1, characterized in that: In the preparation of the modified buffer fiber, the weight ratio of the fused silica glass fiber to the aromatic sulfone fiber in the twisted blending is 1:2-2.5, and the number of the blended fiber strands is 10-14 strands; The length of the chopped composite fiber is 80-90 mm; The weight ratio of the chopped composite fiber to the hydrogen peroxide solution is 1:15-20; The concentration of the hydrogen peroxide solution is 3-3.5wt%.
3. The method for preparing the thermal insulation tile composite material containing a buffer layer according to claim 1, characterized in that: In the preparation of the composite molded body, the chopped length of the aluminum borosilicate fiber, the mullite fiber, and the alumina fiber is 50-70 mm; The calcination temperature of the lower layer body is 1000-1100°C, and the heat preservation calcination time is 2-3h; The ply thickness of the modified buffer fiber is 10-12 mm; The heat preservation and setting time is 10-12h.
4. The method for preparing the thermal insulation tile composite material containing a buffer layer according to claim 1, characterized in that: In the preparation of the composite molded body, the weight ratio of aluminum borosilicate fiber, mullite fiber, alumina fiber, polyacrylic acid, bis(dioctyl pyrophosphate acyloxy)ethylene titanate, and deionized water is 38-40:50-52:12-15:0.6-0.7:3-3.5:3500-3600; The diameter of aluminum borosilicate fiber is 2-3 μm; the diameter of mullite fiber is 4-5 μm; the diameter of alumina fiber is 9-10 μm.
5. The method for preparing the thermal insulation tile composite material containing a buffer layer according to claim 1, characterized in that: In the preparation of the toughened shell, the depth of the toughened coating penetrating into the buffer layer of the composite molded body is controlled to be 0.7-0.75 mm; The heat preservation and curing temperature is 110-115℃, and the heat preservation and curing time is 4-5h; The weight ratio of terminal hydroxyl polysiloxane, nano silicon carbide and cyclohexane is 100:8.5-9:72-76.
6. The method for preparing the thermal insulation tile composite material containing a buffer layer according to claim 1, characterized in that: In the dipping molding, the vacuum degree of vacuum dipping is 0.04-0.05MPa, and the vacuum dipping time is 2-3h; The standing time at room temperature is 10-12h; The temperature is kept at 90-95℃ for 9-10 hours; Calcination: In an argon atmosphere, calcine at 400-450°C for 2-2.5 hours.
7. The method for preparing the thermal insulation tile composite material containing a buffer layer according to claim 1, characterized in that: In the impregnation molding, the volume ratio of the composite precursor to the impregnation liquid is 1:1.8-2; The weight ratio of sodium bicarbonate, hexadecyltrimethylammonium chloride, modified hafnium carbide, deionized water, phenolic resin, and silane coupling agent KH-550 is 1.2-1.3:0.5-0.6:7.5-8:55-58:100-105:13-15; The phenolic resin is a phenolic resin prepolymer with a molecular weight of 300-400.
8. The method for preparing the thermal insulation tile composite material containing a buffer layer according to claim 1, characterized in that: In the preparation of the modified hafnium carbide, the dripping time of the second liquid is controlled to be 30-40 minutes; The weight ratio of nano hafnium carbide to anhydrous ethanol is 1:80-85; The mass concentration of pyromellitic dianhydride in the first liquid is 4-4.1wt%; The mass concentration of 4,4'-diaminodiphenyl ether in the second liquid is 3.5-3.6wt%; The weight ratio of the nano-hafnium carbide to the pyromellitic anhydride in the first liquid and the 4,4'-diaminodiphenyl ether in the second liquid is 83-85:56.5-57:51.5-52.
9. A thermal insulation tile composite material containing a buffer layer, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Thermal-insulation and energy-saving material and cement plate thereof
CN104829192A
Bullet-proof helmet with honeycomb block structure and preparation method of bullet-proof helmet
CN108332614A